2006
DOI: 10.2337/dc06-0495
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Hypoglycemia During Exercise in Children With Type 1 Diabetes by Suspending Basal Insulin

Abstract: OBJECTIVE -Strategies for preventing hypoglycemia during exercise in children with type 1 diabetes have not been well studied. The Diabetes Research in Children Network (DirecNet) Study Group conducted a study to determine whether stopping basal insulin could reduce the frequency of hypoglycemia occurring during exercise.RESEARCH DESIGN AND METHODS -Using a randomized crossover design, 49 children 8 -17 years of age with type 1 diabetes on insulin pump therapy were studied during structured exercise sessions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(31 citation statements)
references
References 13 publications
1
28
0
2
Order By: Relevance
“…While many clinicians may recommend temporary reductions in overnight basal rates in pump-treated patients to reduce the risk of hypoglycemia on nights after afternoon exercise, there are no clear guidelines for the duration and extent of reduction in basal rates, which is likely to vary from patient to patient and depends on the type of exercise. It is not surprising that previous reports have shown that use of this strategy often results in nocturnal hyperglycemia (22,23). …”
Section: Discussionmentioning
confidence: 89%
“…While many clinicians may recommend temporary reductions in overnight basal rates in pump-treated patients to reduce the risk of hypoglycemia on nights after afternoon exercise, there are no clear guidelines for the duration and extent of reduction in basal rates, which is likely to vary from patient to patient and depends on the type of exercise. It is not surprising that previous reports have shown that use of this strategy often results in nocturnal hyperglycemia (22,23). …”
Section: Discussionmentioning
confidence: 89%
“…Although hypoglycemia decreased by discontinuing the insulin pump during exercise, significant rebound hyperglycemia was observed (3). …”
mentioning
confidence: 99%
“…Other studies have recently described exercise-induced reductions in plasma glucose of similar magnitude in patients with type 1 diabetes treated with insulin pumps [33]. Moreover, strategies to prevent exercise-induced reductions in plasma glucose by reducing the basal rate of insulin infusion failed [14,15,34] similar to our attempt to achieve this with "preventive" carbohydrate snacks. In our study, the amounts of carbohydrate administered to our patients were substantial and correspond roughly with published recommendations: Nathan et al [16] recommended 13 g of carbohydrates, preferably in the ▶Fig.…”
Section: Discussionmentioning
confidence: 81%